2022
DOI: 10.1111/1751-7915.14008
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of plant‐based dairy alternatives by lactic acid bacteria

Abstract: Summary Ethical, environmental and health concerns around dairy products are driving a fast‐growing industry for plant‐based dairy alternatives, but undesirable flavours and textures in available products are limiting their uptake into the mainstream. The molecular processes initiated during fermentation by lactic acid bacteria in dairy products is well understood, such as proteolysis of caseins into peptides and amino acids, and the utilisation of carbohydrates to form lactic acid and exopolysaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 135 publications
(171 reference statements)
0
27
0
Order By: Relevance
“…The coexistence of these two species in half of the samples studied suggests a complementary metabolic relationship or functional role within the microbial community of plant-based cheeses. In fact, previous studies have already shown how beneficial the association of these species can be in terms of acidifying capacity and suitability for producing desirable aromatic compounds in the development of plant-based products (Engels et al, 2022; Harper et al, 2022). Further investigation into this relationship could provide more insights to optimize production processes for plant-based cheeses.…”
Section: Resultsmentioning
confidence: 99%
“…The coexistence of these two species in half of the samples studied suggests a complementary metabolic relationship or functional role within the microbial community of plant-based cheeses. In fact, previous studies have already shown how beneficial the association of these species can be in terms of acidifying capacity and suitability for producing desirable aromatic compounds in the development of plant-based products (Engels et al, 2022; Harper et al, 2022). Further investigation into this relationship could provide more insights to optimize production processes for plant-based cheeses.…”
Section: Resultsmentioning
confidence: 99%
“…Acetic acid is also formed during heat treatment of milk (Ng et al, 2021). Acetic acid formed can be a minor product of carbohydrate degradation in the process (Harper et al, 2022). The heat treatment can form significant transitional compounds in coconut milk and reduce them to acetic acid during storage (Vallath & Shanmugam, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Microorganisms like bacteria or fungi produce peptides when plant proteins undergo fermentation. Microbial fermentation can provide a high possibility for producing specific peptides, but the processing duration and contamination risk could increase. Physical approaches, including supercritical fluid extraction, high-pressure processing, , and ultrasound, , microwave-assisted extraction , are examples of other top-down methods. By degrading down protein structures, these techniques allow peptides to be released from plant proteins.…”
Section: The Overview and Production Of Pbpsmentioning
confidence: 99%